2016
DOI: 10.1016/j.chb.2016.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive Internet use and workaholism: An exploratory two-wave longitudinal study

Abstract: Workaholism refers to the uncontrollable need to work and comprises working compulsively (WC) and working excessively (WE). Compulsive Internet Use (CIU), involves a similar behavioural pattern although in specific relation to Internet use. Since many occupations rely upon use of the Internet, and the lines between home and the workplace have become increasingly blurred, a self-reinforcing pattern of workaholism and CIU could develop from those vulnerable to one or the other. The present study explored the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…The prevention of Internet addiction in adults and seniors, as well as the unemployed and mothers on parental leave, who are endangered to a great extent by Internet addiction (Müller, Glaesmer, Brähler, Woelfling, & Beutel, 2013; Young, 1998), has received very little or no attention. These are not yet mentioned in the literature on preventive interventions because such populations are difficult to access or, for example, Internet addiction might be hidden among other problematic behaviors such as workaholism (Quinones, Griffiths, & Kakabadse, 2016). To address the needs of these groups, the type and extent of their problems and developing appropriate interventions for them represent more of a challenge for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of Internet addiction in adults and seniors, as well as the unemployed and mothers on parental leave, who are endangered to a great extent by Internet addiction (Müller, Glaesmer, Brähler, Woelfling, & Beutel, 2013; Young, 1998), has received very little or no attention. These are not yet mentioned in the literature on preventive interventions because such populations are difficult to access or, for example, Internet addiction might be hidden among other problematic behaviors such as workaholism (Quinones, Griffiths, & Kakabadse, 2016). To address the needs of these groups, the type and extent of their problems and developing appropriate interventions for them represent more of a challenge for the future.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, the relationship between off-TAJD and workaholism has not been investigated to date; nevertheless, results in this field sustain a hypothetical positive relationship. Quinones and colleagues [50], in a longitudinal study aimed at investigating the connection between two compulsive behaviours, found a positive relationship between compulsive Internet use at Time 1 and working compulsively at Time 2. Barber and Santuzzi [51] found a positive correlation between workplace telepressure, which is the combination of obsession and urge to immediately reply to work-related ICT messages, and workaholism.…”
Section: Off-work Hours Technology-assisted Job Demandmentioning
confidence: 99%
“…Porter and Kakabadse (2006) conducted a qualitative study with information technology professionals and concluded that work and Internet addiction mutually reinforced one other. This reinforcing mechanism was later examined in a quantitative two-wave study by Quinones, Griffi ths, and Kakabadse (2015), who found that Internet addiction appeared to be the antecedent for work addiction. The authors tentatively explained this result, building on Carnes, Murray, and Charpentier's (2005) model of addiction, via the "masking mechanism" (p. 94).…”
Section: Co-occurring Addictionsmentioning
confidence: 99%